2020
DOI: 10.1097/mat.0000000000001172
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Membrane Oxygenation for Coronavirus Disease 2019 in Shanghai, China

Abstract: Severe cases of coronavirus disease 2019 (COVID-19) cannot be adequately managed with mechanical ventilation alone. The role and outcome of extracorporeal membrane oxygenation (ECMO) in the management of COVID-19 is currently unclear. Eight COVID-19 patients have received ECMO support in Shanghai with seven with venovenous (VV) ECMO support and one veno arterial (VA) ECMO during cardiopulmonary resuscitation. As of March 25, 2020, four patients died (50% mortality), three patients (37.5%) were successfully wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
185
3
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(197 citation statements)
references
References 9 publications
3
185
3
6
Order By: Relevance
“…The Murray score (Table 2) stratifies the severity of acute lung injury and values of greater than 2 should be considered for transfer to centers with ECMO facilities. Patients with ARDS and a Murray score of 3 to 4 may be suitable candidates for ECMO 6 …”
Section: When Should We Use Ecmo In Covid‐19 Patients?mentioning
confidence: 99%
See 1 more Smart Citation
“…The Murray score (Table 2) stratifies the severity of acute lung injury and values of greater than 2 should be considered for transfer to centers with ECMO facilities. Patients with ARDS and a Murray score of 3 to 4 may be suitable candidates for ECMO 6 …”
Section: When Should We Use Ecmo In Covid‐19 Patients?mentioning
confidence: 99%
“…Of these four had died (50%) and three were weaned off ECMO but were still on mechanical ventilation (37.5%). Only one patient had been weaned off ECMO before the 28‐day mark 6 . Zhan et al reported a case of a low‐risk individual who was placed on ECMO therapy within hours of intubation, the clinicians realising early on that mechanical ventilation was insufficient.…”
Section: Current Evidence and Outcomes Of Ecmomentioning
confidence: 99%
“…The role of ECMO for rescue therapy of respiratory failure in critically ill COVID-19 patients remains controversial [10,11,14,15]. In this case report, we present a successful ECMO salvage case in a 51-year-old patient with bilateral SARS-CoV-2 pneumonia and refractory respiratory failure.…”
Section: Discussionmentioning
confidence: 94%
“…Extra-corporeal membrane oxygenation (ECMO) represents a potentially life-saving modality for patients with terminal respiratory failure [9]. However, early experiences from COVID-19 "hot zones" in China reported a high mortality rate of 50-82% in adult patients with ARDS from SARS-CoV-2 pneumonia [10,11]. In the present case report, we describe the successful rescue treatment of a critically ill patient with respiratory failure due to COVID-19 and discuss the critical variables for effective ECMO therapy in this highly vulnerable patient cohort.…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few reports of successful use of venoarterial ECMO in myocarditis secondary to COVID-19. 10 Use of venoarterial ECMO should be based on stringent criteria and subject to scrutiny by ECMO multidisciplinary teams.…”
Section: ■ the Only Recourse If Conventional Ardsmentioning
confidence: 99%